EXPLORING ETHNIC DIVERSITY AS A CATALYST FOR INNOVATION IN MALAYSIA’S PUBLIC HEALTHCARE - Pindaya, Jayagowri; Thambiah, Shanthi; Padzil, Ruhana (SARJANA, 2025)
ABSTRACT This research delves into the influence of ethnic diversity on innovation within Malaysian public healthcare facilities. It explores how ethnic diversity within healthcare teams influence innovation. Employing a mixed-methods approach combining quantitative and qualitative data, this study first conducted multiple regression analysis on survey data collected from healthcare professionals across diverse facilities, followed by in-depth key informant interviews for qualitative exploration and validation of the quantitative findings, to evaluate the influence of ethnic diversity on levels of innovation at various Malaysian healthcare facilities. The results showed a positive correlation between ethnic diversity within healthcare teams and innovation levels. Teams comprising diverse ethnic backgrounds demonstrate a propensity for generating inventive solutions to healthcare challenges and exhibit heightened problem-solving capabilities. The study underscores the significant positive influence of minority ethnic category within teams as a pivotal driver of innovation in Malaysian public healthcare facilities at Ministry, State Health Department, Hospitals, Clinics and Health Institutions. Keywords: Innovation; ethnic diversity; public healthcare sector